Method of Cycloid Gear Tooth Profile Modification of RV Reducer - Zhang Fengshou; Yang Xingxing; Liu Jianting; Li Pengfei (Jixie chuandong)
A kind of eccentricity combined modification method of cycloid gear profile is proposed for solving the problem of the common combination modification method could not simultaneously satisfy the requirements of high bearing capacity and low rotation error. Firstly,based on the precision measurement of the cycloid gear of the RV-40 E reducer with the three-coordinate measuring instrument,the equation of cycloid gear profile is derived by using the method of least square to fit the parameters of the measured cycloid gear tooth profile. And then,by using the optimization function in Matlab,taking the obtained equation curve as the target tooth profile to optimize the cycloid gear profile formed by the three kinds of modification methods that are the combination methods of "eccentricity + isometric + shift","isometric + shift"and "isometric + shift + rotation". Through the comparative analysis,the results indicate that the deviation between the curve obtained by the combined modification of "isometric + shift + eccentricity"and the fitting curve is smaller,compared to the combined modification method of "rotation + isometric + shift"and "isometric + shift",which illustrates the feasibility of the combined modification method of "eccentricity + isometric + shift".